Poverty in Banda Aceh - Daud Bahransyaf (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2017)
Banda Aceh Municipality still has citizens who live in poverty, based on data collection carrieed out in five districts, namely Syiah Kuala, Banda Raya, Lueng Bata, Ulle Kareng and Baiturrahman. Of 600 heads of household identifiedas poor, randomly sampled, it could be seen that there were some fundamental socio economic changes in the income, expenditure, as well as the ownership of goods. Income and expenditure of households in a mounth over Rp 600.000,-.Goods which used to be secondary requirements and owned by middle and upper class society as primary need for life and livelihood could be owned ordinary people, cellphones and motorcycles were mostly owned. TV over 14â€ and refrigerator Here already owned by most respondents. Electricity as a means of lighting and other electrical uses have been utilized by most of the poor families in five districts selected. The electric facility have reached and enjoyed by citizens in the municipality of Banda Aceh. That empirical facts need to be observed and studied further as an input to make adjustments to the areas and criteria of a new definition of poverty for related institutions, central government, local government rule, as well as related minister regulation, specifically the municipality of Banda Aceh.